Midwife Competency Standards and Midwife Authority in Emergency Delivery Services - Noviyanti Noviyanti; Endang Wahyati Yustina; Tammy J. Siarif (SOEPRA, 2021)
Abstract: Midwife as a professional has Competency standards of midwife consist of nine competencies which organize basic knowledge, additional knowledge, and skills of midwives in providing services. Midwife authorities are currently regulated under PMK No. 1464 in 2010 concerning License and Operation of Midwives Practice in which emergency authority during labour is limited by the conditions of the place. This study uses an approach method that is normative juridical, it is a way of examining law research conducted over reading materials or merely secondary data and using the method of deductive thinking as well as the criterion of coherence truth. Not every assessment in labour can be performed independently by midwives. Based on the competency standards of the midwife in Kepmenkes 369 in 2007 concerning the standard of the midwifery profession, competencies required in a midwife profession covers a very wide knowledge and skills, while the authorities of the profession can be said limited. In terms of their presence in a city close to secondary/ tertiary health care facilities, their role is very limited. Reviewing aspects of applicability of the law, it is not limited by space and time, so that there is a consistency of law, law certainty, therefore, relates to the regulation of competency standard that is associated with midwife authority becomes inconsistent.Keyword: Midwife, Competency, Authority, and Emergency in Labor Abstrak: Bidan sebagai tenaga profesional memiliki Standar kompetensi bidan yang terdiri dari sembilan kompetensi yang mengatur pengetahuan dasar, pengetahuan tambahan, dan keterampilan bidan dalam memberikan pelayanan. Kewenangan bidan saat ini diatur dalam PMK No. 1464 Tahun 2010 tentang Perizinan dan Penyelenggaraan Praktek Bidan dimana kewenangan darurat selama persalinan dibatasi oleh kondisi tempat. Penelitian ini menggunakan metode pendekatan yang bersifat yuridis normatif, yaitu suatu cara pemeriksaan penelitian hukum yang dilakukan atas bahan bacaan atau data sekunder semata dan menggunakan metode berpikir deduktif serta kriteria kebenaran koherensi. Tidak setiap pengkajian dalam persalinan dapat dilakukan secara mandiri oleh bidan. Berdasarkan standar kompetensi bidan dalam Kepmenkes 369 tahun 2007 tentang standar profesi bidan, kompetensi yang dibutuhkan dalam profesi bidan meliputi pengetahuan dan keterampilan yang sangat luas, sedangkan kewenangan profesi dapat dikatakan terbatas. Dalam hal kehadiran mereka di kota yang dekat dengan fasilitas kesehatan sekunder/tersier, peran mereka sangat terbatas. Meninjau aspek keberlakuan undang-undang, tidak dibatasi oleh ruang dan waktu, sehingga ada konsistensi hukum, kepastian hukum, oleh karena itu terkait dengan pengaturan standar kompetensi yang dikaitkan dengan kewenangan bidan menjadi tidak konsisten.Kata Kunci: Bidan, Kompetensi, Wewenang, dan Kegawatdaruratan Dalam Persalinan